واقع تناول المنشطات لدى لاعبي رياضة كمال الاجسام ومدى وعيهم بمخاطرها فئة 25-30سنة - قربوز, يونس; رابح, خيرة (Institut d'Éducation Physique et Sportive - Mostaganem 2023/2024, 2024)
تهدف دراستنا الحالية إلى البحث في واقع تناول المنشطات من طرف ممارسي رياضة كمال الأجسام الباغ سنهم بين 25 و30 سنة بولاية غليزان، حيث تم إجراء الدراسة ميدانيا بذات الولاية ببعض صالات كمال الأجسام بها وقد تم اختيار العينة بطريقة قصدية منتظمة، وللوصول إلى نتائج هذه الدراسة اعتمدت الطالبة التساؤل التالية: • ما مستوى وعي ممارسي رياضة كمال الأجسام بآثار تناول المنشطات؟ وتندرج تحت هذا التساؤل الرئيسي تساؤلات فرعية: - ما هي دواعي تناول ممارسي كمال الأجسام للمنشطات؟ - هل هناك وعي لدى رياضيي كمال الأجسام بآثار تناول المنشطات؟ وللوصول للإجابة على هذه التساؤلات اعتمدت الطالبة أداة الاستبيان ومن خلاله طبقت المنهج الوصفي التحليل وهو المنهج الذي تراه الطالبة مناسبا للدراسة، حيث وبعد تفريغ الاستمارة توصلت إلى النتائج التالية: أن رياضيي كمال الأجسام بصالات ولاية غليزان يتناولون المنشطات لغرض التحضير لمنافسة رغم أنها لا تطور الجسم في مدة قصيرة، فالمنشطات تساعد في نشاط الجسم لفترة قصيرة فقط ليس إلا وهي ما يجعل الرياضي يحس بالقوة في تلك اللحظات يدرك الرياضي مدى تأثير تناول المنشطات على جسمه مع طول الزمن ومواصلة تناولها. ومن هذا يمكننا تأكيد فرضية بحثنا أن رياضي كمال الأجسام يعي الآثار التي تسببها المنشطات بتناوله لها. رياضي كمال الأجسام واعي وعلى علم بماهية المنشطات أي أنه ملم بسلبياتها وإيجابياتها. // // // // // Study summary: Our current study aims to investigate the reality of doping by bodybuilding practitioners aged between 25 and 30 years in the state of Relizane. The study was conducted in the field in the same state in some of its bodybuilding gyms, and the sample was chosen. In an intentional and systematic manner, and to reach the results of this study, the student adopted the following question: - What is the level of bodybuilding practitioners’ awareness of the effects of taking steroids? - Under this main question, there are sub-questions - What are the reasons for bodybuilders to take steroids? - Is there awareness among bodybuilding athletes of the effects of taking steroids? In order to answer these questions, the student adopted the questionnaire tool and through it applied the descriptive analysis method, which is the method that the student deems appropriate for the study, where and after By completing the questionnaire, I reached the following results: Bodybuilding athletes in the gyms of the state of Relizane take steroids for the purpose of preparing for a competition, even though they do not develop the body in a short period. Steroids help in the body’s activity for a short period only, and they are what makes the athlete feel strong in those moments. This is the main motivation for eating these substances that are harmful to health over a long period of time. The athlete realizes the impact of taking steroids on his body over time and continues to take them. From this we can confirm our research hypothesis that the bodybuilding athlete is aware of the effects that...Caused by taking stimulants. The bodybuilding athlete is aware and aware of the nature of steroids, meaning he is aware of their negative aspects And its positives.
LES-2024-38
Keywords: وعي- رياضة كمال الأجسام- المنشطات // // awareness – bodybuilding - steroids